The Role of Lead Business Analyst in the Contemporary Enterprise Reporting Process - Lidija Grdošić; Ammar Avdić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The term business intelligence can be defined as a group of widely used ICT tools that gather all kinds of complex data concerning a certain organisation and compiles them into reports that are meaningful, exact and delivered on time. Those tools can provide meaningful insights into the state of an entire organisation. They are used in many different areas: from identifying the most profitable group of clients, business regions, sales in different branches, products to improving cross-sell activities. Most people working for those organisation that do not participate in those processes are not fully aware how to work with those systems neither how much time it is necessary to pass from the disclosed business problem to report which will then be delivered to the necessary personnel. In the process of writing this paper, the theoretical background of BI and its use within the organisation will be emphasised, as well as the role of lead business analyst. Processes that occur in the companies from the idea of a report to its fulfilment will be explained and the overview of main responsibilities of lead business analyst will be given by analysing and gathering job adverts posted at LinkedIn.
Keywords: M12; M15; 330; business intelligence; organisation; enterprise reporting; information; data; knowledge; ad-hoc reporting; BI processes; lead business analyst